2011
DOI: 10.1194/jlr.e013417
|View full text |Cite
|
Sign up to set email alerts
|

Human low density lipoprotein: the mystery of core lipid packing

Abstract: LDL particles are very fascinating macromolecular assemblies of apolipoprotein B-100 and lipids and their structural features have attracted the attention of scientists for decades. There is a general consensus in the literature that LDL particles are organized into two major compartments, namely an apolar lipid core, comprised primarily of cholesteryl esters, triglycerides, and some free unesterifi ed cholesterol and an outer amphipathic shell that surrounds the apolar core. This outer shell is composed of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In advanced lesions, necrosis of macrophages and VSMCs forms a protective fibrous cap surrounding a lipid-rich core. The LDL present in the lipid core are mainly composed of cholestearyl esters and TG in an apolar core [39,40], and surrounded by a polar monolayer of phospholipids in the surface [41]. According to the MALDI-MSI data shown here, TG, glycerophospholipids (PA) and sphingolipids (SM and PE-Cer) are located in calcified regions ( Figure 1).…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…In advanced lesions, necrosis of macrophages and VSMCs forms a protective fibrous cap surrounding a lipid-rich core. The LDL present in the lipid core are mainly composed of cholestearyl esters and TG in an apolar core [39,40], and surrounded by a polar monolayer of phospholipids in the surface [41]. According to the MALDI-MSI data shown here, TG, glycerophospholipids (PA) and sphingolipids (SM and PE-Cer) are located in calcified regions ( Figure 1).…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…For example, SAXS results for measurements of in vitro oxLDL particles showed no major structural changes in samples oxidized with copper for <25 h (23). Over the past 40 years, knowledge about lipoprotein structure has expanded considerably, but several questions about cholesterol packing in the inner region of LDL particles and the conformational orientation of apolipoproteins remain (24)(25)(26). Recent studies with cryomicroscopy point to a lamellar organization of cholesterol in the inner region of LDL particles and to the influence of triglycerides on the temperature at which the transition from this lamellar phase to a disorganized one occurs (27).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of rHDL and rsHDL dynamics, as determined by EINS (rHDL vs. rsHDL in Figure 1) with two other plasma lipoproteins previously studied using EINS:VLDL vs. LDL (Figure 1 in [5]), revealed that VLDL and rHDL (the bigger lipoprotein particles in the two pairs) were softer and more flexible than LDL and rsHDL at ambient temperature, respectively. During VLDL maturation into LDL, the more dynamic triglycerides were removed, and the more rigid cholesteryl esters were incorporated, leading to apoB100 protein rearrangement and particle shrinking (e.g., from~50 nm to~20 nm [73,74]). Similarly, rsHDL particle was smaller and more compact than rHDL (8.3 vs. 9.6 nm, respectively), was rich in cholesteryl esters, and had more protein content (apoA-I or apoA-II).…”
Section: Discussionmentioning
confidence: 99%